2022
DOI: 10.22495/jgrv11i1siart1
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance mechanisms and earnings quality: Is firm size a moderation variable?

Abstract: The main objective of this research is to analyze the influence of independent commissioner, audit committee, managerial ownership, and institutional ownership on earnings quality. This study also observes the role of a firm’s size as a moderating variable. Using specific considerations, the number of the sample is reduced to 20 out of 144 companies from manufacturing companies listed in the Indonesian Stock Exchange during 2013–2016. The data analysis in this research used moderating regression. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…Therefore, it can be concluded that Hypothesis H 2 is not supported. The research findings are not consistent with prior research that supports this hypothesis (Andriani et al, 2021;Purnamasari & Fachrurrozie, 2020;Solikhah et al, 2022). These research findings are also not consistent with legitimacy theory, which explains that companies need to maintain their reputation in order to maintain legitimacy.…”
Section: Resultscontrasting
confidence: 89%
See 2 more Smart Citations
“…Therefore, it can be concluded that Hypothesis H 2 is not supported. The research findings are not consistent with prior research that supports this hypothesis (Andriani et al, 2021;Purnamasari & Fachrurrozie, 2020;Solikhah et al, 2022). These research findings are also not consistent with legitimacy theory, which explains that companies need to maintain their reputation in order to maintain legitimacy.…”
Section: Resultscontrasting
confidence: 89%
“…Furthermore, Kumala and Siregar (2021) argued that large companies tend to have higher earnings quality. In the Indonesian context, prior research found that firm size had a positive influence on earnings quality (Andriani et al, 2021;Purnamasari & Fachrurrozie, 2020;Solikhah et al, 2022). Andriani et al (2021) argued that large companies need to provide a good signal by improving earnings quality to reduce information asymmetry.…”
Section: The Relationship Between Firm Size and Earnings Quality In I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, independent directors may have an incentive to adjust the direction and the performance of opportunistic managers (Khan et al, 2012). In this regard, independent board members can be seen as an effective supervisory tool that contributes to controlling manager's behavior (Solikhah et al, 2022), and reducing agency costs (Naciti, 2019). Additionally, they may play a key role in increasing the levels of information disclosures in firms (Carnini Pulino et al, 2022).…”
Section: Board Independence and Csrmentioning
confidence: 99%
“…Values are given based on predetermined criteria. The banking GCG value is then calculated by comparing the total value obtained with the highest score (Solikhah et al, 2022;Suryati, 2020). According to previous research, company size is a scale for determining the size of a company entities which is viewed through total asset, total revenue, total sales for a year, and so on which describes a company's wealth (Clarisa & Pangerapan, 2019;Putra & Wilopo, 2018).…”
Section: Introductionmentioning
confidence: 99%